PENERAPAN PRINSIP GOOD FAITH BAGI DIREKSI PERSEROAN TERBATAS BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - Siltami, Frisa Ayu; Hanifah, Mardalena; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The Directors shall be acting in good faith and responsibly in conducting management of the Company. It was done based on a standard of liability (standard of duty) the most high as stated by law. in this case the role was based beliefs that include, scrupulous, good faith, condor. Related to the case of a lease which is wrapped around the former director of PT Merpati Nusantara criminalizing directors of the company, especially in terms of decision-making led to a loss for the company when making such decisions based on good faith, and in accordance with the articles of association of the company. Article 97 Paragraph 5 of the Company Law says that the Board of Directors shall be take a responsibility for the loss of the Company if the directors can prove that in doing the maintenance company and the decision has been based in good faith and with prudence for the benefit and in accordance with the purposes and objectives of the company the.The research objective of this thesis, namely; First, the application of the principles of Good Faith in the Company Law. Secondly, legal certainty for directors of limited liability company that runs the principles of Good Faith by the Company Law.This type of research is a normative legal research. In a normative legal research, the author have examined the legal issues by using normative research on the principles of law.From the results of research and discussion of the problem there are 2 main things that can be inferred. First, the application of the principles of good faith in leading the Company's directors as stipulated in Article 97 of the Company Law. Although the Company Law acknowledges the existence of the principle of good faith, but no details of the Company Law and the details regarding the principle of good faith (good faith). Second, protection of legal certainty for directors in making a business decision has been regulated in Article 97 paragraph (5) of the Company Law, but in practice there are still many problems could be found for their interpretations in terms of the notion of state finances and state assets causing disharmony between the Company regulations and other regulation so that directors are acting in good faith for taking care of the company is hard to get legal certainty. Suggestions Author, First, should be made a special regulation governing the standard of good faith is not just for company directors, but for the organ of the company such as the AGM and the board of directors in order to create legal certainty for the organ of the company in carrying out their respective duties. Secondly, it needs to be harmonization of all four of the Act by changing the understanding of the State assets are separated state finances and to revise the law.Keywords: Principles of Good Faith, Directors, Limited Liability Company